Exploring cost of living, learning environment, financial aid and academic achievement influencing well-being among B40 university students. - Shamsuddin, Noorazzila; Nik Md Salleh, Nik Sarina; Mat Zin, Sakinah; Hamid, Roseliza; Zulqernain, Nurul Syaqirah (International Journal of Accounting, Finance and Business, 2025)
This study scrutinizes the cost of living, learning environment, financial aid and academic achievement influencing well-being among B40 university students. The quantitative cross-sectional is employed to measure the relationship between these variables and students' well-being. The study involved a survey methodology to collect data, using a set of developed questionnaires as the main tool for gathering information from participants. The sample consisted of 157 students from Universiti Teknologi MARA (UiTM) who were selected through random sampling to avoid bias and ensure each participant had an equal opportunity to be included. The results showed a moderate positive relationship between cost of living and learning environment factors toward students’ well-being while financial aid and academic achievement factors are not statistically significant relationships with students’ well-being. Regardless of limitations, this research contributes to a better understanding of student's well-being especially for monetary needy students. It is vital for policy makers as well as educational providers to interrelate these factors in improving the university student’s well-being